Predictive Capabilities of Corotating Interaction Regions Using STEREO and Wind In‐Situ Observations. Issue 7 (29th June 2022) - Chi, Yutian; Shen, Chenglong; Scott, Christopher; Xu, Mengjiao; Owens, Mathew; Wang, Yuming; Lockwood, Mike
Abstract: Solar wind stream interaction regions (SIRs) and corotating interaction regions (CIRs) can cause geomagnetic storms and change energetic particle environment, ionospheric composition on Earth. Therefore advanced warning of SIRs/CIRs is vital for mitigating the effect of space weather on critical infrastructures in modern society. Recently, several solar missions, for example, Vigil mission (Luntama et al., 2020) and Solar Ring mission (Wang et al., 2020), that can be served as a space weather monitor, have been proposed. To evaluate the capabilities of these future missions of predicting SIRs/CIRs, the Solar Terrestrial Relations Observatory (STEREO‐B) spacecraft is used to investigate the correlation between SIRs/CIRs detected by STEREO‐B and Wind spacecraft. The correlation coefficients of solar wind velocity in SIRs/CIRs are significantly higher than that of magnetic field intensity or plasma density. It indicates that the velocity structure of solar wind is more persistent than magnetic field and ion density. By assuming the SIR/CIR structures are stable and ideal corotation, 58.9% of SIRs/CIRs in the STEREO‐B CIR catalog can be used to predict CIR arrival time in near‐Earth space. With increasing longitudinal and latitudinal separations between STEREO‐B and Wind, the percentage of accurately predicted CIRs decreases gradually from 100% to 20%. If the separation angle between STEREO‐B and Wind is within 30° in longitude and approximately ±5° in latitude, more than 93.2% of SIRs/CIRs can be accurately predicted several days in advance. This demonstrates that a spacecraft situated 30° trailing Earth in its orbit, can optimize our space weather‐predicting capabilities for the Earth and lessen the risk of missing or "false alarms" CIRs. Plain Language Summary: Stream interaction regions (SIRs) are formed by the interactions between the fast solar wind streams originating from coronal holes and slow solar wind streams. SIRs can corotate with the sun and they can also be called as Corotating Interaction Regions (CIRs), if those structures recur on successive solar rotations. When SIRs/CIRs reach the Earth, they may cause recurrent geomagnetic storms, alter the energetic particle environment around the Earth, and other meteorological processes in Earth's lower atmosphere, posing a threat to satellite systems, radio communications, electrical transmission, and technological critical infrastructure. As a result, the analysis and forecast of when SIRs/CIRs will hit the Earth is a critical issue in the space weather community. This study investigates the prediction ability of SIRs/CIRs with varied longitudinal and latitudinal spacecraft separations using in‐situ measurements from the Solar Terrestrial Relations Observatory (STEREO‐B) and Wind spacecraft. The statistical results reveal that the spacecraft longitudinal and latitudinal separation can have a significant impact on the accuracy of the SIRs/CIRs forecast. According to STEREO‐B in‐situ data, when the latitudinal separation is less than ±5° and the longitudinal separation is less than 30°, more than 93.2% CIR events can be well predicted in advance. Key Points: Spacecraft longitudinal and latitudinal separation can significantly affect the accurate forecast of Corotating Interaction Regions (CIRs) More than 93.2% of CIRs can be reliably predicted in advance with separations of less than 30° longitude and ±5° latitude Most of CIRs arrived at Earth earlier than predicted, when Solar Terrestrial Relations Observatory‐B was located to the south of the Earth in the Heliocentric Earth Equatorial coordinate